Vitex species: review on phytochemistry and pouch design for nutritional benefits / Nur Rejai Salmah Abdul Hakeem … [et al.] - Abdul Hakeem, Nur Rejai Salmah (Penerbit UiTM (UiTM Press), 2016)
Vitex trifolia or locally known as lemuni, is well documented/or its medicinal properties including anticancer, antibacterial and wound healing. For years, the leaves and flowers were consumed for anti-aging and general well-being. It is also commonly served as nutraceuticals to post-partum women during their confinement period. Previous study showed that V. trifolia possesses high antioxidant properties that could prevent oxidative stress related diseases such as cancer, atherosclerosis, diabetes and many more. From the literature, V. trifolia leaves are used as poultice for rheumatic pains, sprains, antithelmintics and inflammations. Meanwhile, the fruits are utilised in amenorrhea. The roots, on the other hand, are used for the treatment of cough and fever. The plant is known to possess pharmacologically-active constituents such as the essential oil, halimanetype diterpenes, flavonoids, triterpenes, lignans, iridoids and ecdysteroids. Review papers were consistently published to justify the non-exhaustive biological exploration of this genus. Nevertheless, only 11 per cent of the total Vitex species were phytochemically examined. Apart from being eaten raw or blanched, Vitex is also taken as a food colourant in preparing lemuni rice. The process of making lemuni rice is quite tedious. First, the leaves and flowers are picked and washed. Both parts are then ground with water and sieved to give a bluish extract which is then mixed with rice and boiled to cook Hence, the Vitex pouch is introduced to provide an easy way to prepare lemuni rice. This packaging is designed to enclose Vitex samples in a pouch that simply can be placed together with rice and boiled to cook Such instant preparation will hopefully promote the consumption oflemuni rice among busy locals. Future plans include international marketing and production of other Vitex nutritional products.